The use of lexical strategies in the discourse of Malaysian advertisements - Baharum, Nur Syauqina; Abdul Halim, Hazlina; Mamat, Roslina; Hasan, Hamisah Zaharah (Persatuan Linguistik Malaysia, 2019)
Today, advertising is the most popular money making industry and companies would actively participate to ensure that their products or services get sold. Due to the competition in advertisements among companies, it is important that they produce effective advertisements. One of the common strategy used by advertisers are the use of lexical strategy. Thus, this study was conducted to determine the significance on the use of lexical strategies in the discourse of Malaysian advertisements and to determine the influences of lexical strategy on the advertising of beauty products in the discourse of Malaysian advertisements. The respondents for this study were students from various faculties at Universiti Putra Malaysia (UPM) who represented different background and culture. A total of 100 questionnaires were distributed by using an online tool of GoogleForm. The questionnaire had adopted the Leech’s theory on lexical strategies that was introduced in 1966 which were divided into the study of verb phrase, noun phrase, adjective compound, morphology, weasel words and neologism. The questionnaire was made up of three different section in relation to the objectives. The application of Leech (1966) is also used to make the questions for respondents. The results for this study shows that the respondents agreed with the significant use of lexical strategy in Malaysian advertisements and had positively agreed to the fact that lexical strategy influenced Malaysian beauty standard. Such study is significant to contribute to future research and also to advertisers.